Ответы и объяснения

2016-11-02T17:29:16+00:00
3,8-(1,6-1,2х)=9,6+(3,7-5х)

3,8-1,6+1,2х=9,6+3,7-5х

2,2+1,2х=13,3-5х

1,2х+5х=13,3-2,2

6,2х=11,1

Х=11,1: 6,2

Х= 11 1/10 : 6 2/10

Х= (10•11+1)/10: (10•6+2)/10

Х=111/10: 62/10

Х=111/10• 10/62

Х=111/1• 1/62

Х=111/62= 1 49/62

Проверка
3,8-(1,6- 1,2• 1 49/62)=9,6+ (3,7-5• 1 49/62)
3,8- 1,6+ 12/10• 111/62= 9,6+ 3,7- 5• 111/62

2,2+ 6/10• 111/31= 13,3- 555/62

22/10+ 666/310=133/10- 555/62

(22•31)/(10•31)+ 666/310= (133•31)/(10•31)- (555•5)/(62•5)

682/310+ 666/310= 4123/310- 2775/310

1348/310=1348/310

4 108/310= 4 108/310

4 54/155= 4 54/155